PENGEMBANGAN LKS FISIKA BERBASIS STARTER EXPERIMENT APPROACH (SEA) PADA MATERI KARAKTERISTIK GELOMBANG UNTUK SMA KELAS XI - Ria Asih Mulyani; Vina Serevina; Raihanati Raihanati (PROSIDING SEMINAR NASIONAL FISIKA (E-JOURNAL), 2016)
The purpose of the research is to develop student’s worksheet based on Starter Experiment Approach (SEA) for high school grade XI in the wave characteristics subject. The method used the Research and Development (R & D) by using the model design of ADDIE. Student worksheets were developed include, 1) title, 2) instructions for use, 3) goals, 4) theory of brief, 5) tools and materials, and last 6) The steps from based on Starter Experiment Approach (initial experiment, observation, problem formulation, provisional estimates, experimental testing, drafting, lesson notes, application of the concept). The steps of the researchers in developing the student worksheet are the analysis, design the media, manufacture the media, revision and refinement. The result from the observation to the school with using quetionnaire at 31 Senior High School Jakarta with 72 students and 4 teachers respondent (100%), known that 95% (67 students) supporting the idea of ​​teaching materials of SEA worksheets in the wave characteristics subject and 89% (64 students) want the development of physics worksheet in the basis of Starter Experiment Approach in the wave characteristics subject. Retrieval of data validation using the instrument in the form of a questionnaire to the physics experts, media experts and teachers. The results of the research with the development of student worksheets based on Starter Experiment Approach in the wave characteristics subject can be used as a physics learning support. Keywords: Student worksheet, Starter Experiment Approach, ADDIE.